2019
DOI: 10.1177/1071100719834539
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Minimum Clinically Important Difference (MCID) in Visual Analog Scale (VAS) Pain and Foot and Ankle Ability Measure (FAAM) Scores After Hallux Valgus Surgery

Abstract: Background: Minimum clinically important difference (MCID) defines a threshold when determining clinically significant treatment improvement. Visual analog scale (VAS) and Foot and Ankle Ability Measure activities of daily living (FAAM-ADL) are commonly used for measuring hallux valgus correction. This study aimed to determine MCID in VAS pain and FAAM-ADL scores for hallux valgus correction and additionally, to identify variables influencing achievement of the VAS pain MCID. Methods: Patients undergoing hallu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 29 publications
4
38
0
1
Order By: Relevance
“…In addition, Sutton et al and Landorf et al have previously determined the minimal clinical important difference (MCID) of foot and ankle surgeries. The authors determined that a difference in VAS score of 0.8 can be considered the MCID [24, 25]. In our study, the difference between two groups in VAS score at 24 h and 48 h were 2.28 points and 1.18, respectively.…”
Section: Discussionmentioning
confidence: 47%
“…In addition, Sutton et al and Landorf et al have previously determined the minimal clinical important difference (MCID) of foot and ankle surgeries. The authors determined that a difference in VAS score of 0.8 can be considered the MCID [24, 25]. In our study, the difference between two groups in VAS score at 24 h and 48 h were 2.28 points and 1.18, respectively.…”
Section: Discussionmentioning
confidence: 47%
“…Although statistically significant (a F-value of 10.4 in the time effect with an ES of 0.54), the amount of emotional improvement measured on a VAS was 3 mm (51 to 54 mm). Although limited to quantifying pain, previously established minimal differences on VAS were at least 15 mm [30] or 18 mm [31]. Based on that, the overall degree of emotional improvement after a single session in our study is not clinically meaningful.…”
Section: Discussionmentioning
confidence: 55%
“…is is also in accordance with the higher VAS scores of Meta2 (6.57) and Meta3 (5.72) ( Table 2). However, the previous literature report showed that the VAS index of Meta was slightly more than 5 [24].…”
Section: Discussionmentioning
confidence: 83%
“…Corresponding to the higher pain percentage of Meta2-3 in the four groups (Figure 4), the VAS pain score increased significantly with increased severity of HV deformity ( Table 2). Previous studies found a positive correlation between HV deformity and metatarsal pain levels [18,24]. Increasing HV severity was also significantly associated with greater Meta pain and decreased foot function [25].…”
Section: Discussionmentioning
confidence: 86%